Human parvovirus B19, varicella zoster virus, and human herpes virus 6 in temporal artery biopsy specimens of patients with giant cell arteritis: analysis with quantitative real time polymerase chain reaction. Issue 5 (15th April 2005) - Álvarez-Lafuente, R; Fernández-Gutiérrez, B; Jover, J A; Júdez, E; Loza, E; Clemente, D; García-Asenjo, J A; Lamas, J R
Abstract : Objective: To evaluate the role of parvovirus B19 (B19), varicella zoster virus (VZV), and human herpes virus 6 (HHV-6) in the aetiopathology of giant cell arteritis (GCA). Methods: Temporal artery biopsy specimens from 57 patients with GCA and 56 controls were investigated. DNA was obtained by biopsy, and quantitative real time polymerase chain reaction assay performed to establish the prevalence and viral load of B19, VZV, and HHV-6. Amplification of the human β-globin gene was used as internal positive control. Results: ( a ) B19 was detected in 31/57 (54%) patients (median viral load 45.2 (25th–75th centiles 0–180.2) copies/μg DNA) v 21/56 (38%) controls (median viral load 0 (0–66.7) copies/μg of DNA; p = 0.07 for DNA prevalence, p = 0.007 for viral load. Among 31 B19 positive samples, 21 (68%) patients with biopsy proven GCA had >10 2 B19 copies/μg of DNA v 5/21 (24%) controls; p = 0.001. ( b ) No significant difference was found for VZV (p = 0.94 for DNA prevalence; p = 0.76 for viral load) and HHV-6 (p = 0.89 for DNA prevalence; p = 0.64 for viral load) in the GCA group compared with controls. Conclusion: B19 may have a role in the aetiopathology of GCA, particularly in those patients with high viral load; no evidence was found for VZV and HHV-6.